Dissemination of multiple carbapenem-resistant clones of Acinetobacter baumannii in the Eastern District of Saudi Arabia - Al-Sultan, Abdulrahman A.; Evans, Benjamin A.; Aboulmagd, Elsayed; Al-Qahtani, Ahmed A.; Bohol, Marie Fe F.; Al-Ahdal, Mohammed N.; Opazo, Andres F.; Amyes, Sebastian G. B. (Frontiers in Microbiology, 2015)
It has previously been shown that carbapenem-resistant Acinetobacter baumannii are frequently detected in Saudi Arabia. The present study aimed to identify the epidemiology and distribution of antibiotic resistance determinants in these bacteria. A total of 83 A. baumannii isolates were typed by PFGE, and screened by PCR for carbapenemase genes and insertion sequences. Antibiotic sensitivity to imipenem, meropenem, tigecycline and colistin were determined. Eight different PFGE groups were identified, and were spread across multiple hospitals. Many of the PFGE groups contained isolates belonging to World-wide clone 2 (WW2). Carbapenem resistance or intermediate resistance was detected in 69% of isolates. The blaVIM gene was detected in 94% of isolates, while blaOXA-23-like genes were detected in 58%. The data demonstrate the co-existence and wide distribution of a number of clones of carbapenem-resistant A. baumannii carrying multiple carbapenem-resistance determinants within hospitals in the Eastern Region of Saudi Arabia.